EFFECTIVE USE OF INNOVATIVE PEDAGOGICAL TECHNOLOGIES IN THE STUDY OF VOCABULARY IN PRIMARY CLASSES (On the example of the study of Number) - Azimov Shokhrukh Shukhratjon ogli; Urolov Sarvar Bakhtiyorovich (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article provides information on the methods of effective use of innovative pedagogical technologies in the study of vocabulary in primary classes. There are also several techniques used in the study of vocabulary in primary classes.